First-principles study of Al2Sm intermetallic compound on structural, mechanical properties and electronic structure - Lin, Jingwu; Wang, Lei; Hu, Zhi; Li, Xiao; Yan, Hong (Solid state communications, 2017)
The structural, thermodynamic, mechanical and electronic properties of cubic Al2Sm intermetallic compound are investigated by the first-principles method on the basis of density functional theory. In light of the strong on-site Coulomb repulsion between the highly localized 4f electrons of Sm atoms, the local spin density approximation approach paired with additional Hubbard terms is employed to achieve appropriate results. Moreover, to examine the reliability of this study, the experimental value of lattice parameter is procured from the analysis of the TEM image and diffraction pattern of Al2Sm phase in the AZ31 alloy to verify the authenticity of the results originated from the computational method. The value of cohesive energy reveals Al2Sm to be a stable in absolute zero Kelvin. According to the stability criteria, the subject of this work is mechanically stable. Afterward, elastic moduli are deduced by performing Voigt-Reuss-Hill approximation. Furthermore, elastic anisotropy and anisotropy of sound velocity are discussed. Finally, the calculation of electronic density of states is implemented to explore the underlying mechanism of structural stability. •Al2Sm intermetallic was systematically investigated by first-principle method.•Mechanically properties and elastic anisotropy were well described and discussed.•Phonon velocities and Debye temperature were calculated and analyzed.•Electronic structure of Al2Sm was visually presented and analyzed.